Culturally relevant programming versus the status quo: a meta-analytic review of the effectiveness of treatment of indigenous offenders - Gutierrez, Leticia (Canadian journal of criminology and criminal justice, 2018)
The over-representation of Indigenous peoples in criminal justice systems internationally remains a critical issue. Some have argued that replacing generic services with culturally relevant programming would be an effective strategy to address this problem. This meta-analysis examines the effectiveness of culturally relevant programs for Indigenous offenders compared to conventional programs. Results based on seven studies (N = 2,732) indicate Indigenous offenders who participate in these programs have significantly [End Page 321] lower odds of recidivism (odds ratio = 0.72) compared to Indigenous offenders who participate in generic programs. Although considerable methodological limitations were observed in the studies reviewed, the results of this metaanalysis are consistent with the concept of specific responsivity and the notion that treatment effectiveness is maximized when the learning environment is engaging and relevant. Additional research of higher methodological quality is needed to further evaluate culturally relevant programs and determine with greater confidence how correctional interventions best work for this population.